Diagnóstico situacional para identificar los posibles Problemas Turísticos en el Cantón Pujilí - Risueño Hinojosa, Verónica Alexandra (2019)
Ecuador is a country with enormous natural diversity, possessor of multiple tourist attractions that attract the attention of locals and foreigners, in recent years tourism has become one of the most important activities carried out in Ecuador that allows the creation of new sources of employment and economic development for the places where it develops. The Pujilí Canton is part of one of the seven cantons of the provinces of Cotopaxi, located in the second most populated canton of the province, it has seven parishes that are Angamarca, Guangaje, La Victoria, Pilaló, Tingo la Esperanza, Zumbahua, each of these places carries out different economic activities, for which the present project had as purpose to know and investigate the tourist problems that the Pujilí canton presents by making a situational diagnosis of the place, through the collection of primary and secondary information, through interviews with key actors and revisions of the PDYOT, identifying that the Pujilí canton has 172 tourist stables divided into accommodation meals and drinks and recreation also has 17 cultural and natural manifestations that helped the carrying out the analysis of both urban and rural parishes in a consolidated manner, for which the PEST-LA matrix was used, allowing the realization of a table of problems in the social, cultural and environmental fields, with which we were able to identify what are the lacks of the canton giving us as a result an excellent inequality ad in the execution of the other public, the lack of establishments suitable for tourism, and the little interest on the part of the authorities and the population in the development of tourism since they do not consider it as an activity that generates economic resources for which It is essential to know the tourist problems in order to be able to find solutions and seek the support of public and private entities the problems already encountered in the realization of this project, enhancing the cultural and natural attractions already identified in order to execute it.